Customer Intention to Use M-Banking in Indonesia - Wana, Desty; Noviriani, Eliza; Dewi, Dinda Rintania (RSF Conference Series: Business, Management and Social Sciences, 2025)
Heightened rivalry in today’s digital banking landscape compels banks to fully grasp the elements shaping customer decisions to embrace mobile banking. The objective of this research is to examine the relationship between perceived security, ease of use, and trust, and their impact on customer intention to use m-banking in Indonesia. This research aims to expand knowledge on the elements that influence the adoption of mobile banking apps in emerging digital technology locales. A quantitative method with causal associations was employed for this study. The study’s participants comprised bank customers, from whom a sample of 100 individuals was selected using a targeted sampling strategy. Information was gathered via surveys and subsequently assessed utilizing Eviews software version 12 for regression analysis. The results of the study indicate that partially perceived security has a significant effect on customer intention in using m-banking, perceived ease of use has no significant impact on customer intention in using m-banking, and perceived trust has a significant effect on customer intention in using m-banking. Simultaneously, the three independent variables of perceived security, perceived ease of use, and perceived trust have a substantial impact on customer intention in using m-banking. Considering these discoveries, tactics intended to boost the acceptance of mobile banking should prioritize the enhancement of safety measures and customer confidence, potentially by integrating dual authentication protocols, more robust data encryption techniques, consistent educational initiatives concerning digital safety, and the establishment of efficient and prompt channels for addressing concerns.